Pyrosequencing Reveals Changes in Soil Bacterial Communities after Conversion of Yungas Forests to Agriculture - Montecchia, Marcela Susana (2015)
The Southern Andean Yungas in Northwest Argentina constitute one of the main biodiversity hotspots in the world. Considerable changes in land use have taken place in this ecoregion, predominantly related to forest conversion to croplands, inducing losses in above-ground biodiversity and with potential impact on soil microbial communities. In this study, we used high-throughput pyrosequencing of the 16S ribosomal RNA gene to assess whether landuse change and time under agriculture affect the composition and diversity of soil bacterial communities. We selected two areas dedicated to sugarcane and soybean production, comprising both short- and long-term agricultural sites, and used the adjacent native forest soils as a reference. Land-use change altered the composition of bacterial communities, with differences between productive areas despite the similarities between both forests. At the phylum level, only Verrucomicrobia and Firmicutes changed in abundance after deforestation for sugarcane and soybean cropping, respectively. In cultivated soils, Verrucomicrobia decreased sharply (;80%), while Firmicutes were more abundant. Despite the fact that local diversity was increased in sugarcane systems and was not altered by soybean cropping, phylogenetic beta diversity declined along both chronosequences, evidencing a homogenization of soil bacterial communities over time. In spite of the detected alteration in composition and diversity, we found a core microbiome resistant to the disturbances caused by the conversion of forests to cultivated lands and few or none exclusive OTUs for each land-use type. The overall changes in the relative abundance of copiotrophic and oligotrophic taxa may have an impact in soil ecosystem functionality. However, communities with many taxa in common may also share many functional attributes, allowing to maintain at least some soil ecosystem services after forest conversion to croplands.